The Role of Field Experiments in Studies of Dune Dynamics and Morphology - Lancaster, Nicholas (Annals of Arid Zone, 2016)
Field measurement of aeolian process-form interactions in the desert have provided in recent years many new informations on the characteristics of the dune-building winds and their patterns of interaction with the dune forms. It is now confirmed that flow acceleration along the dune slope leads to increased sediment flux towards the crest as well as net erosion. Dune shape and the wind direction in relation to the dune determine the pattern of lee side airflow and sand flow pattern there. Information on these and many other relationships have helped to understand how the different dune types interact with the wind regimes and evolve over space and time.